How corruption in government affects public welfare: A review of theory - Johann Lambsdorff (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2001)
The objectives of government are pivotal to understanding the diverse negative effects of corruption on public welfare. Corruption renders governments unable or unwilling to maximize welfare. In the first case, it distorts agents' decisions and limits the contractual space available to agents and the government, acting as a benevolent principal. In the second case, a corrupt principal creates allocative inefficiencies, cripples its credible commitment to effective policies, and opens the door to opportunism.
Keywords: D61; D72; K4; 330; Corruption; welfare; principal-agent-theory; rent-seeking; x-inefficiency; kleptocracy; opportunism